A területi finanszírozás harmonizációja - Perger, Éva (Tér és Társadalom, 1998)
Adjustment of financial system in regional policy includes two main issues such as adaptation of the Hungarian system to EU regulations and spatial harmonisation of national systems. Financial techniques and mechanisms should be brought nearer to the European one to accelerate the enlargement, to make the national system more efficient and enhance the expected benefits of our joining. Since the Hungarian financial system is being adapted to the EU regulation rapidly, national characteristics and objectives must be defined and articulated. Financial reforms should be nin in parallel with favourable changes in the spatial development such increasing regional cohesion and transformation of territorial administration. Joining the European Union involves changes in mechanisms of local and territorial fmances. The shift towards a decentralised system should be supported for the following reasons: mechanism of fmancial support in the EU rests on territorial basis, since European regional development projects must be supported by local/regional sources, that of communities and regions should be enhanced, reforms of the fmancial system in the EU shall put more emphasis on regional aspects of development. There is an urgent need for considering territorial aspects in the national system of financial decision-making to further extent to ease regional disparities and sectoral pressure on the redistribution furthermore, to define short term and long lasting objects in spatial development. For this purpose, territorial aspects should be regarded as essential elements of the redistribution, financial resources of community services and regional development should be distinguished and managed separately, legal and economic framework of spatial development must be defined furthermore, national development purposes and policies should be also revised.